Psychological correlates of sleep quality in lung cancer patients under chemotherapy: A single‐center cross‐sectional study. Issue 9 (18th July 2019) - Papadopoulos, Dimitrios; Kiagia, Maria; Charpidou, Andriani; Gkiozos, Ioannis; Syrigos, Konstantinos
Abstract: Objectives: Disturbed sleep is a common complaint of lung cancer patients undergoing active oncologic treatment. We aimed to clarify the extent to which psychological symptoms, coping strategies, and social support interfere with sleep quality and whether they mediate the relationship between sleep quality and fatigue or functional capacity in a sample of chemotherapy treated lung cancer patients. Methods: Lung cancer patients attending an oncology unit for scheduled chemotherapy cycles completed questionnaires assessing their sleep quality, fatigue, depression, anxiety, stress, coping, social support, symptoms of pain, dyspnea, and cough, and sleep hygiene practices. Demographic and disease‐related characteristics were obtained from patients' medical records and treating physicians rated their functional status. Multivariate regression and mediation analyses were applied to test the study's hypotheses. Results: One hundred nineteen patients were enrolled, 58.2% of whom were identified as poor sleepers. After adjusting for age, gender, comorbidities, concomitant medications, cancer stage, prior and ongoing treatment, sleep hygiene, and symptoms, there was a statistically significant association between poor sleep quality and anxiety (odd`s ratio [OR] 1.17 [95% CI, 1.01‐1.35]), stress (OR 1.14 [95% CI, 1.04‐1.25]), and positive coping (OR 1.15 [95% CI, 1.02‐1.31]). Poor sleep quality was an independent correlate of fatigue ( B 1.56 [95% CI, 0.61‐2.50]) and low performance status (OR 5.17 [95% CI, 1.60‐16.72]); stress symptoms partially mediated the relationship between sleep quality and fatigue ( P = .030). Conclusions: Higher psychological burden predict sleep disturbances and contribute to increased fatigue in lung cancer patients undergoing chemotherapy. Effective psychoeducational interventions may benefit these populations.